Down to Earth (2011)
This year, 25 Knowledge Expeditions groups, divided into 15 topics of interest, formulated and developed their research projects. Trade-interested expeditioners and companies chose sneakers for their research because they sensed that, when buying them, not only personal tastes were decisive.